2017
DOI: 10.1039/c7tb00634a
|View full text |Cite
|
Sign up to set email alerts
|

In situ synthesis of NIR-light emitting carbon dots derived from spinach for bio-imaging applications

Abstract: NIR-light emitting CDs (R-CDs) were prepared using spinach as a precursor by one-step solvothermal treatment. The R-CDs exhibited great optical properties, negligible toxicity, and superior labelling capability both in vitro and in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(49 citation statements)
references
References 48 publications
1
48
0
Order By: Relevance
“…[15] As an additional benefit, natural biomass can covertl ow-value biomass into useful materials. [16] Biomass usually contains heteroatoms, such as Na nd S, which is ag ood choice to prepare heteroatomdoped CDs, [17] such as spinach, [18] soy milk, [19] honey, [20] and cabbage. [21] In our group, we used Hypocrellabambusae as precursors to prepare hydrophilic CDs for bimodalf luorescence (FL)/photoacoustic imaging-guided synergistic PDT/PTT.…”
Section: Introductionmentioning
confidence: 99%
“…[15] As an additional benefit, natural biomass can covertl ow-value biomass into useful materials. [16] Biomass usually contains heteroatoms, such as Na nd S, which is ag ood choice to prepare heteroatomdoped CDs, [17] such as spinach, [18] soy milk, [19] honey, [20] and cabbage. [21] In our group, we used Hypocrellabambusae as precursors to prepare hydrophilic CDs for bimodalf luorescence (FL)/photoacoustic imaging-guided synergistic PDT/PTT.…”
Section: Introductionmentioning
confidence: 99%
“…porphyrin molecules). 34,35 Moreover, it is also observed that the uorescence intensity of the blue-emission band is much weaker than those of the red-emission band. It is well known that the naked eye is much more sensitive to red light than to the blue one.…”
Section: Optical Properties Of D-cdsmentioning
confidence: 99%
“…More in detail, the HR XPS spectrum of C 1s indicates the presence of C-C/C=C (284.1 eV), C-N (285.9 eV), C-O (286.9 eV), C=N/C=O (288.5 eV) and N-C=O (289.9 eV) ( Figure 3f) [49,59]. The HR XPS spectrum of N 1s contains three components that can be assigned to pyrrolic N (399.0 eV), graphite N (400.6 eV) and amino N (401.2 eV) ( Figure 3g) [60,61]. The HR XPS of O 1s spectrum was deconvoluted into three peaks at 530.9 eV, 532.6 eV and 533.7 eV, corresponding to -OH, C=O and N-C=O, respectively (Figure 3h) [59,62].…”
Section: Morphologies and Structure Analyses Of Aa-cdsmentioning
confidence: 99%